Rediscovery of Rhipsalis ewaldiana Barthlott & N.P. Taylor (Cactaceae): notes of morphology and conservation of an endemic and threatened species from the Brazilian Atlantic Forest - Gonzaga, Diego Rafael; Moraes, Lucas; Vasconcelos, Lucas Veronezi Feitosa De; Reis, Ricardo Carneiro Da Cunha (Phytotaxa, 2018)
Cactaceae Juss. is a family which comprises 124 genera and about 1438 species distributed from Canada to Patagonia, with the largest diversity in tropical and subtropical regions of Americas (see e.g., Hunt et al. 2006). The flora of Brazil includes 39 Cactaceae genera and 261 species, of which 14 genera and 54 species can be found the Rio de Janeiro state, highlighting the importance of this state to the biodiversity of Brazilian cacti (see BFG 2015). These species are highly affected by anthropic disturbances, which cause rapid habitat destruction, especially affecting the narrowly distributed endemic taxa, with 31% of the family being threatened, demonstrating the high anthropogenic pressures on the biodiversity in arid lands (Goettsch et al. 2015).